Evaluation of the School Literacy Movement Program in Senior High School - Heru Santosa; Supadi (Jurnal Penelitian dan Pengembangan Pendidikan, 2023)
The government launched a school literacy program at the education level to increase students' interest in reading and writing. This study was conducted to analyze how the literacy program works. This research is using CIPP evaluation model. The method used in this study is a qualitative research method with an evaluation research design by conducting observations, interviews, and examining program implementation documents. Sources of information were obtained through interviews with principals, educators, and students. The research results on the context component show that the CIPP of the School Literacy Movement of senior high school was successfully implemented. The literacy program is implemented with stages 1) Habituation of reading non-lesson books for 15 minutes before learning begins. 2) Learning with foreign language book reading activities, be it English, French, and Japanese books. 3) Development by requiring grade XII students to write a novel with a target of 1 school year which will be printed in April. These three stages follow the School Literacy Movement (GLS) guidelines.